(untitled) (Proceeding of Dakwah Saizu International Conference, 2023)
In the current VUCA era, where Artificial Intelligence (AI) has made remarkable advancements, it is not surprising that its influence has also extended to the realm of religion. One sector that has experienced significant impact is the field of religious preaching (dakwah), where AI technology has paved the way for new developments in disseminating religious messages. The research method employed is the Library Research method. Library Research is a qualitative research type that focuses on analysis and adopts an emic perspective. Facing a future era of dakwah influenced by AI technology within the VUCA framework, it is crucial to understand that technology serves as a tool, not an ultimate goal. The core mission of dakwah remains centered on spreading religious messages, deepening understanding, and fostering positive societal changes. Therefore, the use of AI technology in dakwah should be directed towards supporting these core objectives.